Profiling Key Phytoconstituents in Screw-Pressed Nigella Solid Residue and Their Distribution in Products and Byproducts During Oil Processing - Parbat Raj Thani; Joel B. Johnson; Surya Bhattarai; Tieneke Trotter; Kerry Walsh; Daniel Broszczak; Mani Naiker (Applied Sciences)
Nigella sativa L. (generally known as black cumin) is a medicinal plant prized for its therapeutic and nutritional benefits. Its seed oil is used extensively in pharmaceuticals, nutraceuticals, cosmetics, and cooking. However, extracting oil to satisfy the world’s needs leaves behind plenty of solid residues. The seeds of Nigella are loaded with health-benefiting phytoconstituents, but so might their extraction residues. While much research on seeds and oil has been carried out, there is relatively little information about solid residue, particularly regarding health-benefiting phytoconstituents. Additionally, there is a knowledge gap relating to how phytoconstituents transfer from seeds to solid residue during oil extraction and any loss of key phytoconstituents that may occur during this transfer. Understanding the health-benefiting phytoconstituents in Nigella solid residue is crucial for unlocking its full potential for value-added applications in health and nutrition. Moreover, understanding the dynamics of these phytoconstituent transfers is essential for optimizing extraction processes and preserving the nutritional and therapeutic value of the derived products. Therefore, this study investigated the composition of the screw-press solid residues of different Nigella genotypes grown under similar environmental conditions. The results showed moderate variation in the levels of potential health-benefitting phytoconstituents in Nigella solid residues regarding total phenolic content (TPC) (720.5–934.8 mg GAE/100 g), ferric reducing antioxidant capacity (FRAP) (853.1–1010.5 mg TE/100 g), cupric reducing antioxidant capacity (CUPRAC) (3863.1–4801.5 mg TE/100 g), thymoquinone (TQ) (156.0–260.1 mg/100 g), saturated fatty acid (SFA) (2.0–2.2 mg/g), monounsaturated fatty acid (MUFA) (2.0–3.6 mg/g), and polyunsaturated fatty acid (PUFA) (8.2–12.1 mg/g). Notably, TPC, FRAP, and CUPRAC had high transfer rates into the solid residue (78.1–85.9%, 65.4–75.7%, and 84.5–90.4%, respectively), whereas TQ, SFA, MUFA, and PUFA showed lower transfer rates (15.9–19.3%, 7.5–8.9%, 12.0–18.3%, and 6.5–7.5%, respectively). When summing the values of individual phytoconstituents transferred into oil and solid residue from their respective seeds during processing, it was found that only 80.6–88.3% of TPC, 74.2–84.4% of FRAP, 86.3–92.3% of CUPRAC, 54.4–64.9% of TQ, 68.5–92.4% of SFA, 76.2–90.6% of MUFA, and 51.6–76.6% of PUFA were transferred from the total value present in their respective seeds.